ON TRENDS IN THE DEVELOPMENT OF MILITARY OPERATIONS IN MODERN MILITARY CONFLICTS - Abduvakhobov B. M.; Shamsiddinov U. N. (American Journals Publishing, 2023)
In article on the base of analysis main facts of the environment, determined new form and methods of the conduct defense. Defined the problem questions, determined basic confrontation, suggested the ways to their solutions.
Keywords: Fighting attempt, mountain region, geographic and climate environment, mountain relief, mountain peak, shun radiation, high, factory, skills and ways, mines field and engineering obstacles, width of defence, depth of defense.